Single-layer, cascaded and broadband-heat-dissipation metasurface for multi-wavelength lasers and infrared camouflage - Xingdong Feng; Tianqi Zhang; Xuejun Liu; Fan Zhang; Jianjun Wang; Hong Bao; Shan Jiang; YongAn Huang (Opto-Electronic Advances, 2025)
The combination of advanced photoelectric detectors has rendered single-band camouflage materials ineffective, necessitating the development of infrared multispectral camouflage. However, the design and fabrication of existing works remain complex as they usually require the integration of multiscale structures. Here, we introduce phase modulation into the infrared camouflage metasurfaces with metal-dielectric-metal configuration, enabling them to achieve camouflage across more bands. Based on this strategy, a simple but effective single-layer cascaded metasurface is demonstrated for the first time to achieve low reflection at multi-wavelength lasers, low infrared radiation in atmospheric windows, and broadband thermal management. As a proof-of-concept, a 4-inch sample with a minimum linewidth of 1.8 μm is fabricated using photolithography. The excellent infrared multispectral camouflage performance is verified in experiments, showing low reflectance in 0.9–1.6 μm, low infrared emissivity in mid-wavelength infrared (MWIR) and long-wavelength infrared (LWIR) bands, and high absorptance at the wavelength of 10.6 μm. Meanwhile, broadband high emissivity in 5–8 μm can provide high-performance radiative heat dissipation. When the input power is 1.57 W∙cm-2, the surface/radiation temperature of the metasurface decreases by 5.3 °C/18.7 °C compared to the reference. The proposed metasurface may trigger further innovation in the design and application of compact multispectral optical devices.